Barttin Regulates the Subcellular Localization and Posttranslational Modification of Human Cl-/H+ Antiporter ClC-5 - Wojciechowski, Daniel; Kovalchuk, Elena; Yu, Lan; Tan, Hua; Fahlke, Christoph; Stölting, Gabriel; Alekov, Alexi K. (Frontiers in Physiology, 2018)
Dent disease 1 (DD1) is a renal salt-wasting tubulopathy associated with mutations in the Cl-/H+ antiporter ClC-5. The disease typically manifests with proteinuria, hypercalciuria, nephrocalcinosis, and nephrolithiasis but is characterized by large phenotypic variability of no clear origin. Several DD1 cases have been reported lately with additional atypical hypokalemic metabolic alkalosis and hyperaldosteronism, symptoms usually associated with another renal disease termed Bartter syndrome (BS). Expression of the Bartter-like DD1 mutant ClC-5 G261E in HEK293T cells showed that it is retained in the ER and lacks the complex glycosylation typical for ClC-5 WT. Accordingly, the mutant abolished CLC ionic transport. Such phenotype is not unusual and is often observed also in DD1 ClC-5 mutants not associated with Bartter like phenotype. We noticed, therefore, that one type of BS is associated with mutations in the protein barttin that serves as an accessory subunit regulating the function and subcellular localization of ClC-K channels. The overlapping symptomatology of DD1 and BS, together with the homology between the proteins of the CLC family, led us to investigate whether barttin might also regulate ClC-5 transport. In HEK293T cells, we found that barttin cotransfection impairs the complex glycosylation and arrests ClC-5 in the endoplasmic reticulum. As barttin and ClC-5 are both expressed in the thin and thick ascending limbs of the Henle´s loop and the collecting duct, interactions between the two proteins could potentially contribute to the phenotypic variability of DD1. Pathologic barttin mutants differentially regulated trafficking and processing of ClC-5, suggesting that the interaction between the two proteins might be relevant also for the pathophysiology of BS. Our findings show that barttin regulates the subcellular localization not only of kidney ClC-K channels but also of the ClC-5 transporter, and suggest that ClC-5 might potentially play a role not only in kidney proximal tubules but also in tubular kidney segments expressing barttin. In addition, they demonstrate that the spectrum of clinical, genetic and molecular pathophysiology investigation of DD1 should be extended.